Vancomycin Hypersensitivity Diagnosed by Lymphocyte Blast Transformation - Nguyen P. Tran; Jeremy Katcher; Erin Rohman; Mary Francis Hall; Christie F. Michael; Isao Miyairi; D. Betty Lew (Case Reports in Pediatrics)
A 15-year-old male admitted for Pott's puffy tumor developed recurrent episodes of fever, diffuse morbilliform rash, eosinophilia, and tubulointerstitial nephritis while on multiple antibiotics. Lymphocyte blast transformation (LBT), a method of detecting cellular immune response by measuring levels of interferon-γ (IFN-γ), was used to diagnose vancomycin hypersensitivity and guide antibiotic selection.